2020
DOI: 10.3390/ijms21228705
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Programming and Reprogramming of Hypertension and Kidney Disease: Impact of Tryptophan Metabolism

Abstract: The concept that hypertension and chronic kidney disease (CKD) originate in early life has emerged recently. During pregnancy, tryptophan is crucial for maternal protein synthesis and fetal development. On one hand, impaired tryptophan metabolic pathway in pregnancy impacts fetal programming, resulting in the developmental programming of hypertension and kidney disease in adult offspring. On the other hand, tryptophan-related interventions might serve as reprogramming strategies to prevent a disease from occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 133 publications
1
48
0
1
Order By: Relevance
“…IDO activity is an index represented by the ratio between the concentrations of kynurenine and tryptophan (Kyn/Trp) [ 33 , 34 , 35 ]. Tryptophan metabolism is also involved in chronic kidney disease (CKD), and kynurenine metabolites are known to be UTx that are increased even in CKD patients [ 36 , 37 ]. In particular, tryptophan catabolism plays a fundamental role in pathways involved in cancer immune resistance.…”
Section: Discussionmentioning
confidence: 99%
“…IDO activity is an index represented by the ratio between the concentrations of kynurenine and tryptophan (Kyn/Trp) [ 33 , 34 , 35 ]. Tryptophan metabolism is also involved in chronic kidney disease (CKD), and kynurenine metabolites are known to be UTx that are increased even in CKD patients [ 36 , 37 ]. In particular, tryptophan catabolism plays a fundamental role in pathways involved in cancer immune resistance.…”
Section: Discussionmentioning
confidence: 99%
“…One example is TMAO, a cardiovascular risk factor and uremic toxins. Additionally, several tryptophan metabolites are known as gut microbiota-derived uremic toxins, such as indoxyl sulfate (IS), indoleacetic acid (IAA), and indoxyl--D glucuronide (IDG) [ 67 ]. These tryptophan-derived uremic toxins have proinflammatory, procoagulant, prooxidant, and pro-apoptotic effects, all of which are implicated in the pathogenesis of CVD [ 68 ].…”
Section: Implications Of Gut Microbiota In the Developmental Origins Of Cvdmentioning
confidence: 99%
“…The composition of the gut microbiota determines several tryptophan metabolites because they are catabolism products of gut microbiota. These tryptophan-derived microbial catabolites are important signaling molecules in the host and the microorganisms ( 24 , 25 ). Targeted metabolomics studies have shown that RCC patients have elevated Kyn pathway metabolites ( 26 ).…”
Section: Discussionmentioning
confidence: 99%